Correlating biological activity to thermo-structural analysis of the interaction of CTX with synthetic models of macrophage membranes - de Araújo Pimenta, Luciana; Duarte, Evandro L.; Muniz, Gabriel S. Vignoli; Pasqualoto, Kerly Fernanda Mesquita; de Mattos Fontes, Marcos Roberto [UNESP]; Lamy, M. Teresa; Sampaio, Sandra Coccuzzo (Springer Nature, 2021)
The important pharmacological actions of Crotoxin (CTX) on macrophages, the main toxin in the venom of Crotalus durissus terrificus, and its important participation in the control of different pathophysiological processes, have been demonstrated. The biological activities performed by macrophages are related to signaling mediated by receptors expressed on the membrane surface of these cells or opening and closing of ion channels, generation of membrane curvature and pore formation. In the present work, the interaction of the CTX complex with the cell membrane of macrophages is studied, both using biological cells and synthetic lipid membranes to monitor structural alterations induced by the protein. Here we show that CTX can penetrate THP-1 cells and induce pores only in anionic lipid model membranes, suggesting that a possible access pathway for CTX to the cell is via lipids with anionic polar heads. Considering that the selectivity of the lipid composition varies in different tissues and organs of the human body, the thermostructural studies presented here are extremely important to open new investigations on the biological activities of CTX in different biological systems.